Vital reproductive indices in non gravid female rabbits treated with crude ethanol extract of spondias mombin (2013)
Ten female Chinchilla breed of rabbits with a mean weight of 1.65 ±0.06 kg, were randomly divided equally into a treatment and a control group. The treatment group received orally 800 mg.kg1 of an ethanol extract of Spondias mombin for fourteen days. The control group received only distilled water utilizing the same method of administration. The females were kept separately away from males. Assays of the reproductive hormones before and after treatment with the extract in the treatment group were done. Both groups were sacrificed after fourteen days of oral administration and their reproductive tracts carefully examined. The studies revealed the normal morphology of ovaries, oviduct, uterine horns, and uterine body in both groups. The histological sections of different reproductive segments were normal. Left and right ovaries appeared to show marked oogenesis in the treated group going by the larger number of follicles observed compared to the control. The body weight adjusted mean paired ovarian diameter of the control group (0.51 +0.02cm) was significantly (P<0.05) different from the treated animals (0.41 ±0.39 cm) but this did not translate into a significant difference in the paired ovarian weights. The body weight adjusted lengths, widths and weights of other parts of the reproductive tracts did not differ significantly comparing the treated and control groups, except for the length of the right uterine horn and the weight of the right oviduct. The studies showed that all of the hormones did not change significantly, comparing the pre and post treatment in the treated group. It was concluded that 800 mg.kg-' of ethanol extract of Spondias mombin appeared to favour folliculogenesis in non-gravid rabbits and resulted in no observed pathological effects on the entire reproductive tract of the rabbit.